Partisipasi Pedagang Pasar Nanggalo dalam Pelaksanaan Tera di Dinas Perdagangan Kota Padang - Syaputra, Rahmade; Eriyanti, Fitri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This research aims to determine the participation of Nanggalo market traders in implementing tera at the Padang City Trade Office. This research was conducted using a qualitative approach with descriptive methods. The results of the research show that the participation of Nanggalo market traders in implementing tera at the Padang City Trade Office is not in accordance with applicable standards and regulations. With the discovery of many measuring instruments/scales that are not marked, there are still many traders who do not know about and do not participate in carrying out tera activities, it is found that there are traders who are reluctant to carry out tera because measuring instruments that are damaged or inaccurate are subject to repair costs, many frauds are found on measuring instruments, as well as the discovery of traders who are reluctant to carry out tera activities because the tera activities result in damage to the trader's measuring instruments.